2022
DOI: 10.1039/d1nj04460e
|View full text |Cite
|
Sign up to set email alerts
|

Ti3C2Tx MXene nanosheets hybridized with bacteriochlorin–carotenoid conjugates for photocatalytic hydrogen evolution

Abstract: Development of efficient photocatalysts with a wide spectral range for photocatalytic hydrogen evolution reaction (HER) is a promising way to address the current energy and environmental crises. In particular, utilization...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Sun et al synthesized a series of bacteriochlorophyll-a (BChl-a) based photocatalysts connected with different carotenoids. [85] The best photocatalytic performance for hydrogen revolution reached 15.5 μmol g À 1 h À 1 , which is much higher than BChl-a itself without connecting with the carotenoid moieties. It is inferred from the EIS test as well as the photocurrent test that the efficient charge transfer and relatively slow electron-hole pairs recombination process at the interface between dyad molecules and MXene.…”
Section: Chlorophyll and Its Derivativesmentioning
confidence: 93%
See 1 more Smart Citation
“…Sun et al synthesized a series of bacteriochlorophyll-a (BChl-a) based photocatalysts connected with different carotenoids. [85] The best photocatalytic performance for hydrogen revolution reached 15.5 μmol g À 1 h À 1 , which is much higher than BChl-a itself without connecting with the carotenoid moieties. It is inferred from the EIS test as well as the photocurrent test that the efficient charge transfer and relatively slow electron-hole pairs recombination process at the interface between dyad molecules and MXene.…”
Section: Chlorophyll and Its Derivativesmentioning
confidence: 93%
“…Sun et al. synthesized a series of bacteriochlorophyll‐ a (BChl‐ a ) based photocatalysts connected with different carotenoids [85] . The best photocatalytic performance for hydrogen revolution reached 15.5 μmol g −1 h −1 , which is much higher than BChl‐ a itself without connecting with the carotenoid moieties.…”
Section: Typical Biohybrid Molecule‐based Photocatalystsmentioning
confidence: 99%
“…), X is carbon and/or nitrogen, and T x are surface terminations (-OH, -O-, and/or -F). 21 They have been applied to a wide array of fields like catalysis, 22 energy, 23,24 biosensors, [25][26][27] and water treatment applications. [28][29][30] The diverse applications of this material are due to its interesting properties like adsorption capacity, large surface area, high electrical conductivity, and good biocompatibility.…”
Section: Introductionmentioning
confidence: 99%
“…Although the sophisticated systems found in nature are fascinating, the examples of photovoltaic devices focusing on the usage of natural chlorophylls (Chls) and bacteriochlorophylls (BChls) have been quite limited compared to other organic functional dyes such as artificial porphyrins or phthalocyanines. Our group has been successfully developed semi-synthetic Chl derivatives toward solar energy applications [7], and besides, recent studies demonstrated the utilization of Chl-based dyes as photocatalysts for water splitting hydrogen evolution [8][9][10][11][12][13] or key components for energy storage devices [14,15] as well as BChlbased sensitizers for OSC [16] and Chl-sensitized TiO 2 electron transport layer for PSC [17]. To reveal the working mechanism of Chl-based BSCs, physical techniques such as sub-picosecond transient absorption spectroscopy and pumpprobe time-resolved absorption spectroscopy were employed [18,19], and an unconventional energy alignment of OSC that disobeyed the classical theory was clarified using a bilayer heterojunction model [20].…”
Section: Introductionmentioning
confidence: 99%